Create a Sherlock Channel. - Williams, Johnathon (Macaddict : a better machine, a better magazine.)
Google is great when you're searching for stuff far and wide, but if you want to limit your searching to a particular site, use Sherlock instead. Of course, you need a Sherlock channed to do the deed-here's how to build one.